Effects of a non-lethal chemical repellent on airport bird communities - Urchek, Kathleen, author; Pejchar, Liba, advisor; Werner, Scott, committee member; Kendall, William, committee member; Bright, Alan, committee member (Colorado State University. Libraries, 2024)
Human-wildlife conflicts are likely to occur wherever the interests and activities of humans and wildlife overlap. Airport environments are a prime example of where such conflict is pervasive because wildlife can view airports as habitat, yet the presence of wildlife increases the risk of collision. As humans increase our reliance on air travel and development encroaches on natural areas, conflicts between humans and wildlife will continue to be prevalent in airport settings, thus creating the need for effective management tools. To assess the effectiveness of one such tool, we evaluated the effect of a non-lethal chemical repellent on bird abundance, species richness, movement, and behavior in airport settings. Following a Before After Control Impact Paired study design we compared the changes among each variable from a period of pre-treatment to a period of active treatment, in both treated and control sites. Using Poisson and zero-inflated mixed effects models we found that the repellent is likely effective in shifting birds from treated to untreated areas within airports, and that the abundance of two common species, Bobolinks and European Starlings, declined following treatment. We also found that the repellent does not change the frequency in which birds move out of treated plots and intersect with runways, but may be altering the within-plot behavior of Eastern Meadowlarks, Red-winged Blackbirds, and Sandhill Cranes. Our mixed findings highlight the need for continued study of the mechanisms behind avian response to chemical repellents in airport settings. Although a diverse set of approaches will always be needed to alleviate the many human-wildlife conflicts associated with airports, here we show that, to promote co-existence with wildlife, this chemical repellent can be a part of that toolset.